Comparative Effectiveness of a 30-minute Online Lecture on Abdominal Ultrasonography in the Post-COVID-19 era: A Multi-center Study - Joonho Jeong; Kwang Il Seo; Hyun Joon Park; Neung Hwa Park (The Korean Journal of Gastroenterology)
Background/Aims: Coronavirus 2019 (COVID-19) accelerated the importance of online learning in the field of medical education. This study compared the impact of online lectures on abdominal ultrasonography (USG) with that of offline lectures and assessed the efficacy of abdominal USG lectures for internal medicine (IM) residents and gastroenterology (GI) fellows. Methods: A 30-minute lecture on upper abdominal USG was delivered online or offline, and a test with 39 short-answer questions was conducted before and after the lecture. Results: The study population included 25 physicians (13 IM residents and 12 GI fellows) in the online group and 23 (20 IM residents, three GI fellows) in the offline group. The rates of USG education experience for online and offline groups were 64.0% and 69.6%, respectively (p=0.919). A significant increase in the test scores was observed after a one-time USG lecture in IM residents in both the online and offline, as well as GI fellows in the online (p<0.0001, <0.0001, and p=0.004, respectively). In addition, the delta scores were similar in the online and offline after a one-time lecture (8.8±4.3 vs. 7.8±3.7, respectively; p=0.406). A comparison of the delta-scores of the IM resident and GI fellow showed no significant difference within either the online or offline (9.0±4.5 vs. 8.4±3.6, p=0.927; 7.3±3.8 vs. 7.3±3.0, p=0.985). Conclusions: The effectiveness of online USG lectures was comparable to that of offline lectures. In addition, a 30-minute, one-time abdominal USG lecture provided value to IM residents and GI fellows.